Serious video games and psychological support: A depression intervention among young cancer patients - Khan, S. (Elsevier B.V., 2022)
Depression, coupled with a cancer diagnosis in early childhood, often leads toward disinclination to psychotherapy, especially in children. However, a possible remedy could be found in video games that could reduce the depressive condition. This study investigates two games and our results show that the ability of therapy embedded game (3D-GIT) is relatively better than the simple serious game (Remission-II) in reducing depressive symptoms associated with a cancer diagnosis. The sample comprised of 60 cancer patients, randomly selected from different cancer hospitals in Pakistan. All the patients were pre-tested using the Center for Epidemiological Studies Depression Scale for Children (CES-DC). The sample was randomly divided into two equal groups: one group played the 3D-GIT game, and the other played the Remission-II game. The games were played four times a week for a month. All the patients were then re-tested on the same scale. Pre-test and post-test scores were compared through paired t-test analysis. The findings of the study support the first two hypotheses that 3D-GIT and Re-Mission-2 are effective in reducing depressive symptoms among young cancer patients. The study results reveal that these video games could be used as an alternative treatment of depression for those who could not or are unwilling to go for counseling sessions with clinical psychologists. However, the results show that there are no significant differences between 3D-GIT and Remission-II games, suggesting that both games effectively reduce depressive symptoms among cancer patients. The study results support that the 3D-GIT game and the Remission-II game could be used to reduce depression among cancer patients. Â© 2022 Elsevier B.V.